Recurrent acute coronary syndrome after infliximab infusion in a patient with rheumatoid arthritis: Case report (Colombia Medica, 2023)
Case description:A 61-year-old male patient with uncontrolled rheumatoid arthritis presented acute coronary syndrome three times less than 48 hours after infliximab infusion.Clinical findings:He presented with ST-elevation myocardial infarction on two occasions and nonST-elevation acute coronary syndrome on one, with the identification of multivessel coronary disease.Treatment and outcome:The coronary intervention was performed with thrombus aspiration, medicated stent implantation, medicated balloon angioplasty, discontinuation of infliximab, and modification and optimization of cardiovascular pharmacological management.Clinical relevance:Patients with rheumatoid arthritis have subclinical cardiovascular disease and increased cardiovascular risk. The evidence regarding the relationship between infliximab and ischemic heart disease is controversial. A broad clinical spectrum of cardiac involvement with infliximab infusion is found in case reports, ranging from stable angina to ST-segment elevation acute coronary syndrome. The pathophysiology is not elucidated, with hypotheses proposing plaque rupture, allergic reactions, and vasoconstriction as possible disease mechanisms. The direct association between infliximab infusion and acute coronary syndrome needs more clinical research to optimize the management and prognosis of patients with this type of complication.